MicroRNA-34a Inhibition Alleviates Lung Injury in Cecal Ligation and Puncture Induced Septic Mice - Chen, Song; Ding, Renyu; Hu, Ziwei; Yin, Xiaohan; Xiao, Feng; Zhang, Wei; Yan, Shijiao; Lv, Chuanzhu (Frontiers in Immunology, 2020)
Sepsis is the leading cause of death in intensive care units. MicroRNA-34a (miR-34a) is involved in sepsis progression, while its underlying mechanisms on sepsis-induced lung injury remain obscure. Oxidative stress, pyroptosis and inhibition of autophagy can result in organ injury. MiR-34a has been reported to regulate oxidative stress and autophagy via inhibiting silent information regulator T1 (SIRT1) and autophagy gene 4B (ATG4B) signaling. This study aimed at identifying the function of miR-34a in oxidative stress, inflammation, pyroptosis and autophagy in sepsis-induced lung injury. Male 8-week-old C57BL/6 mice were subjected to cecal ligation and puncture and treated with miR-34a antagomir/agomir. Survival (n=10), histopathological changes (n=6) and lung wet-to-dry ratio (n=6) were recorded and assayed. Other detection (n=6) was performed to investigate the level of oxidative stress, inflammation, pyroptosis and autophagy in lung tissues. Results showed that miR-34a down-regulation ameliorated lung injury in septic mice as reflected by decreased lung injury scores (decrease from 3.000.32 to 2.000.32) and wet-to-dry ratio (0.36-fold decrease). MiR-34a down-regulation also decreased reactive oxygen species accumulation (0.36-fold decrease), and promoted superoxide dismutase activity and the expression of SIRT1 (1.24-fold increase), heme oxygenase-1 and nuclear factor erythroid 2 like 2 to inhibit oxidative stress in septic mice. Moreover, miR-34a down-regulation suppressed inflammatory response and pyroptosis in septic mice, as evidenced by decreased level of pro-inflammatory factors including tumor necrosis factor α, interleukin-6 (IL-6), IL-1β and IL-18, activity of caspase-1 (0.51-fold decrease) and expression of nucleotide-binding domain and leucine-rich repeat protein-3 (0.48-fold decrease), apoptosis-associated speck-like protein containing a CARD, cleaved-caspase-1 and cleaved-gasdermin D (0.36-fold decrease), and increased level of anti-inflammatory factors IL-10. MiR-34a down-regulation also enhanced autophagy in septic mice as evidenced by more autolysosomes and elevated expressions of ATG4B (0.90-fold increase), beclin1, ATG9 and LC3 II/I. Among these experiments, miR-34a up-regulation showed opposite effects on oxidative stress, inflammatory response, pyroptosis and autophagy in septic mice. Additionally, miR-34a could bind to the 3'-untranslated region of SIRT1 and ATG4B. In conclusion, our findings demonstrated that miR-34a was implicated in oxidative stress, inflammation, pyroptosis and autophagy in the development of sepsis. MiR-34a inhibition had a potential to alleviate sepsis-induced lung injury.